(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The location of the study site for the presented paper here is at Arkansas in the United States of America. Geophysical investigations using seismic refraction tomography (SRT) and multichannel analysis of surface waves (MASW) surveys have been jointly carried out on the basis of an experimental investigation in the field. The motive of this study is to validate and map a postulated fault, in the eastern part of Arkansas in the United State of America. The SRT techniques have shown their potentiality in successfully identifying the fault and generated remarkably similar images of the fault, while the MASW tool generated a slightly different image of the fault due to condition that the earth under survey made up of layers of material that increase in seismic velocity which consider the perfect case for SRT techniques. The results show that the integrated use of seismic refraction tomography and multichannel analysis of surface waves is an effective tool with great potential. They provide very useful data for shallow mapping applications.